Readiness of health professionals for telemedicine implementation: multi-centered cross-sectional study in public hospitals, South Ethiopia - Ibrahim, Yenus; Sako, Sewunet; Ayele, Abdurehman; Glagn, Mustefa (Frontiers in Digital Health, 2025)
BackgroundThe application of telemedicine significantly improves healthcare access and quality. However, its implementation is limited by healthcare professionals’ readiness, particularly in low-income countries like Ethiopia. This study aimed to assess healthcare professionals’ readiness and identify factors influencing it.MethodsAn Institution-based cross-sectional study was conducted among 417 healthcare professionals in six public hospitals in the Gamo zone from July to August 2024. A simple random sampling technique was employed to select the study participants. The data were collected using a Kobo self-administered structured questionnaire and were exported to SPSSv.26 for analysis. Variables with p-values ≤ 0.25 were candidates for multivariable logistic regressions and significance was determined at p-values of <0.05 at a 95% confidence level.ResultHealthcare professionals’ readiness was found to be 68.8%(95%CI: 64.5%–72.8%). Computer access [AOR: 2.23(95% CI: 1.26–3.93)], having adequate knowledge [AOR: 2.01(95% CI: 1.29–3.41)], having a favorable attitude [AOR: 1.96(95% CI 1.23–3.131)], and being female [AOR: 1.782(95%CI: 1.119–2.840)] were significantly associated with readiness of health professionals.ConclusionTwo-thirds of health professionals were ready for telemedicine implementation. To successfully implement telemedicine, it is crucial to prioritize capacity building, improve IT infrastructure, and involve more female healthcare professionals in the process.